The interactions between IC engine thermodynamics and knock. (1st July 2017) - Caton, Jerald A.
Highlights: Importance of engine thermodynamics regarding knock was quantified. Effects of compression ratio, engine speed and EGR on knock was reported. Retarding combustion to avoid knock resulted in decreases of efficiency. Abstract: The development of high efficiency spark-ignition internal combustion engines is often constrained by the occurrence of knock. Knock may result in engine damage, lower performance, and lower efficiency. The options for preventing knock often involve lower compression ratios, lower boost, retarded spark timing, and other design choices that are detrimental to engine performance and efficiency. Since knock is largely a function of the thermodynamic state of the unburned zone, the occurrence of knock is expected to be a strong function of the engine thermodynamics. The purpose of the current work is to couple a simple knock model with a comprehensive engine cycle simulation to determine the interactions between the engine thermodynamics and knock. This work has explored the effects of engine parameters such as compression ratio (4–12), engine speed (500–2500 rpm), inlet pressure (50–100 kPa), exhaust gas recirculation (0–25%), combustion duration and heat transfer on knock. In each case, the occurrence of knock is connected to the cylinder pressures and the gas temperatures of the unburned zone. For example for a compression ratio of 12, to avoid knock the brake thermal efficiency decreased from 36.5% to 34% due to retarding the combustion.